RIFM fragrance ingredient safety assessment β-Patchoulene, CAS Registry Number 514-51-2. (May 2018) - Api, A.M.; Belsito, D.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; La Cava, S.; et al.
Highlights: β-Patchoulene, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read across and/or TTC.